Home » Blog » Prove that a function satisfying a given equation must be the exponential function

Prove that a function satisfying a given equation must be the exponential function

If f(x) is a function defined for all x \in \mathbb{R} and such that

    \[ f'(x) = cf(x) \qquad \text{for all } x \]

prove that we must have

    \[ f(x) = Ke^{cx} \]

for some constant K.


Proof. Let g(x) = f(x)e^{-cx}. Then we can compute the derivative,

    \[ g'(x) = -cf(x)e^{-cx} + f'(x) e^{-cx}. \]

Since we know f'(X) = cf(x) we then have

    \[ g'(x) = -cf(x)e^{-cx} + cf(x)e^{-cx} = 0. \]

Therefore, g(x) = K for some constant K and we have

    \[ K = f(x)e^{-cx} \quad \implies \quad f(x) = Ke^{cx}. \qquad \blacksquare \]

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):